2015
DOI: 10.1186/s13104-015-1285-7
|View full text |Cite
|
Sign up to set email alerts
|

Survey of clustered regularly interspaced short palindromic repeats and their associated Cas proteins (CRISPR/Cas) systems in multiple sequenced strains of Klebsiella pneumoniae

Abstract: BackgroundIn recent years the emergence of multidrug resistant Klebsiella pneumoniae strains has been an increasingly common event. This opportunistic species is one of the five main bacterial pathogens that cause hospital infections worldwide and multidrug resistance has been associated with the presence of high molecular weight plasmids. Plasmids are generally acquired through horizontal transfer and therefore is possible that systems that prevent the entry of foreign genetic material are inactive or absent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 47 publications
3
38
0
Order By: Relevance
“…Moreover, the proportion of L. helveticus spacer sequences that did not show similarity to other sequences contained in GenBank database was about 61%, as observed by Ostria‐Hernandez et al . () for K. pneumoniae . This result could be a consequence of the vast amount of uncharacterized genetic elements in nature as well as a lack of genome and phage sequences belonging to the L. helveticus species (Zago et al .…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Moreover, the proportion of L. helveticus spacer sequences that did not show similarity to other sequences contained in GenBank database was about 61%, as observed by Ostria‐Hernandez et al . () for K. pneumoniae . This result could be a consequence of the vast amount of uncharacterized genetic elements in nature as well as a lack of genome and phage sequences belonging to the L. helveticus species (Zago et al .…”
Section: Resultsmentioning
confidence: 98%
“…Also, Ostria‐Hernandez et al . () found that 13% of spacer sequences retrieved in CRIPSR loci from Klebsiella pneumoniae was similar to sequences of phages, whereas only 8 and 5% from plasmids and Klebsiella genome sequences respectively. Similarly, some of the spacer sequences in L. helveticus were like more than one region of the same phage or genome sequence (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CRISPR arrays were identified from genome assemblies using the CRISPR Recognition Tool v1.2 96 and genomes with >3 putative arrays were investigated manually to check for spurious identifications and/or identifications of single arrays split over multiple assembly contigs. Nucleotide sequences for the previously described Kp cas genes 97 were extracted from the NTUH--K2044 reference chromosome (accession: NC_012731.1). Genomes were screened for novel cas genes by HMM domain search using the domain profiles developed by Burstein and colleagues 98 (HMMER v3.1b2, bit score ≥200 99 ).…”
Section: Crispr/cas and Restriction--modification Systemsmentioning
confidence: 99%